Acute coronary syndrome in the young Nepalese population with their angiographic characteristics - Shankar Laudari; Sachin Dhungel; Laxman Dubey; Rajesh Panjiyar; Madhu Gupta; Gagnapatnam Subramanyam; Pawina Subedi; Bindesh Ghimire (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Acute coronary syndrome (ACS) is an emerging cardiac problem in the young population in Asia and Nepalese population is not an exception to this. Early ACS in young age imparts huge familial and social economic burden. Early identification and proper management strategy is still a challenging problem in developing countries like Nepal where there are limited coronary intervention centers. The study was conducted with objective to study the clinical spectrum, etiologies, coronary angiographic characteristics and their clinical outcomes. Materials & Methods:  This is a cross-sectional study carried out in a tertiary hospital in central Nepal. Forty patients with acute coronary syndrome with age less than 40 years were enrolled in the study. Results: Majority of the patients were males with male: female=1.8:1. Twenty six (65%) patients were having ST segment elevation myocardial infarction followed by non-ST elevation myocardial infarction in nine (22.50%) patients and unstable angina in five (12.50%). patients. The most common risk factors were smoking, systemic hypertension, diabetes mellitus and dyslipidemia. Majority were having single vessel disease. Twenty (50%) patients had undergone primary angioplasty followed by thrombolysis in seven patients and the rest were managed medically because of late presentation. In-hospital major adverse cardiac events and mortality were higher among STEMI than NSTEMI and unstable angina. Conclusion: Acute coronary syndrome in the young is increasing in the Nepalese population. This group of population should be well educated and made aware of the potential coronary risk factors and their modification.